Pengaruh Baca Tulis Al-Qur’an terhadap Prestasi Belajar pada Mata Pelajaran Pendidikan Al-Qur’an Hadis - Sri Handayani; Winda Maulidah (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2022)
The purpose of this study was to determine the implementation of learning to read Al-Qur'an Can Affect the ability of students to read Al-Qur'an at grade 1 students at Madrasah Ibtidaiyah. This research method uses quantitative methods using a correlational approach. Based on the results of testing the correlation coefficient obtained price r = 0.633. Based on the product moment correlation table guidelines used, it can be said that between variables X and Y there is a moderate or sufficient correlation. Based on the test results known t count = 4.63 and t table ( = 0.01: 32) = 2.70 (with interpolation). This means t arithmetic> t table. Thus that the proposed hypothesis is accepted, namely that there is a positive and significant correlation between learning to Read the Qur'an and the ability to read the Qur'an. To find out the contribution of variable X to variable Y, the formula Kd = r2 x 100% is used. The determinant coefficient figure of 40.1% shows that the contribution of learning to read and write the Koran to the Learning Achievement of the Education of the Al-Qur'an Hadith is equal to 40.1% while the rest (100% -40.1% = 59.9% ) is influenced by other factors not analyzed Keywords: Al-Qur'an, literacy, learning, education, learning achievement